Integrating agriculture policies with climate change strategies and commitments in Nepal - Chaudhary, Arbind; Babu, Suresh Chandra; Srivastava, Nandita (International Food Policy Research Institute, 2025)
The world continues to grapple with acute hunger, malnutrition, poverty, income inequality, and other crises. In 2023, approximately 864 million people experienced severe food insecurity (FAO et al. 2024). On the one hand, poor policy adoption disrupts market and supply chain vulnerabilities, exacerbates food insecurity, and causes economic instability and crises (Hélène and Cohen 2020). On the other hand, disasters and extreme weather conditions significantly damage available infrastructure, transportation networks, and storage facilities, disrupting the distribution of agricultural commodities and as well as regular food patterns (Hasegawa et al. 2021). The COP28 UAE Declaration on Sustainable Agriculture, Resilient Food Systems, and Climate Action recognizes that agriculture and food systems must urgently adapt and transform to meet the challenges of climate change. It commits to integrating agriculture and food systems into climate action while simultaneously mainstreaming climate action across policy agendas and actions related to agriculture and food systems (UNFCCC 2023).